Successful research supervision : advising students doing research - Lee, Anne. (London : Routledge, 2012)
'A fabulous resource for graduate advisors' Eric Mazur, Harvard University Successful Research Supervision offers a research-based practical framework for academics to be able to examine and further develop their effectiveness as research supervisors. Research supervisors working in all levels of higher education must ensure that their students gain efficiencies from working as part of an effective cohort and develop high levels of interdisciplinary understanding and critical thought. To impart these disciplines effectively is essential for any successful research supervisor. From helping researchers to begin to managing a project through to successful completion, this book guides the reader through a series of exercises to identify their individual strengths and weaknesses and then provides theoretically sound advice in a practical and easy to use format. Successful Research Supervision is full of examples of the best practice from outstanding scientists, social scientists and humanities supervisors from both the UK and the USA. This book will encourage and help academics to: - Expand their own repertoire and array of actions and responses, thus giving them the flexibility to meet different situations with ease and confidence - Identify the optimum combination of approaches to best fit individual students - Understand the influence of their own value and experiences in the choice of their approach to research students - Be able to choose the most appropriate combination of approaches for a particular curriculum or project - Employ a neutral language for developing and assisting others'--
Includes bibliographical references and index.
Keywords: Graduate students -- Supervision of; Faculty advisors; Dissertations, Academic